To solve the equation 8/9(x + 1/2) = 32/3 for x, we can start by simplifying both sides.
We can first multiply both sides of the equation by 9/8 to eliminate the fraction on the left side:
(9/8) * (8/9)(x + 1/2) = (9/8) * (32/3)
(x + 1/2) = 4
Now, we need to isolate x on one side of the equation. We can do that by subtracting 1/2 from both sides.
(x + 1/2) - 1/2 = 4 - 1/2
x = 3.5
Therefore, the solution to the equation 8/9(x + 1/2) = 32/3 is x = 3.5.
What What is is the the solution of the equation 8/9(x + 1/2) = 32/3 when solving for ?
3 answers
It's wrong
Apologies for the mistake. Let's solve the equation correctly:
To solve the equation 8/9(x + 1/2) = 32/3 for x, we can start by simplifying both sides:
8/9(x + 1/2) = 32/3
We can multiply both sides of the equation by 9 to eliminate the fraction on the left side:
(8/9)(x + 1/2) * 9 = (32/3) * 9
Simplifying, we have:
8(x + 1/2) = 32 * 3
Distribute 8 on the left side:
8x + 8/2 = 96
Simplify:
8x + 4 = 96
Now, subtract 4 from both sides:
8x = 96 - 4
8x = 92
Finally, isolate x by dividing both sides by 8:
x = 92/8
Simplifying, we get:
x = 11.5
Therefore, the solution to the equation 8/9(x + 1/2) = 32/3 is x = 11.5.
To solve the equation 8/9(x + 1/2) = 32/3 for x, we can start by simplifying both sides:
8/9(x + 1/2) = 32/3
We can multiply both sides of the equation by 9 to eliminate the fraction on the left side:
(8/9)(x + 1/2) * 9 = (32/3) * 9
Simplifying, we have:
8(x + 1/2) = 32 * 3
Distribute 8 on the left side:
8x + 8/2 = 96
Simplify:
8x + 4 = 96
Now, subtract 4 from both sides:
8x = 96 - 4
8x = 92
Finally, isolate x by dividing both sides by 8:
x = 92/8
Simplifying, we get:
x = 11.5
Therefore, the solution to the equation 8/9(x + 1/2) = 32/3 is x = 11.5.